Macrophage migration inhibitory factor gene influences the risk of developing tuberculosis in northwestern Colombian population (2007)
Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine that regulates innate and adaptative immunity responses against pathogens. The MIF gene, at 22q11.2, is polymorphic. Functional promoter variants in the MIF gene influence susceptibility to inflammatory diseases in Caucasians and Africans. An association study was carried out to examine the influence of MIF -173 single nucleotide polymorphism and the MIF -794 microsatellite on the susceptibility to develop human tuberculosis (TB) in a well-defined Latin-American population. To this purpose, 230 northwestern Colombian patients with pulmonary TB, negative for human immunodeficiency virus infection, and 235 matched healthy individuals stratified by the tuberculin skin test were examined. Multivariate analysis showed that MIF -173C allele was associated with disease (odds ratio = 1.64, 95% confidence interval 1.07-2.52) in a dominant pattern. No allele in the MIF -794 CATT microsatellite was associated with risk of TB. These results indicate that MIF gene influences the risk of developing TB in the studied population. © 2007 Blackwell Munksgaard.